2023
DOI: 10.1101/2023.01.19.23284811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude and practice (KAP) and risk factors on dengue fever among children in Brazil, Fortaleza: A cross-sectional study

Abstract: Background Dengue fever is a mosquito-borne viral disease that is associated with four serotypes of the dengue virus. Children are vulnerable to infection with the dengue virus and the risk of severe dengue disease is the highest among infants and children, particularly those who have been previously infected with a different dengue serotype. Sufficient knowledge, positive attitudes, and proper practices (KAP) are essential for dengue prevention and control. This study aims to estimate the dengue seropositivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“… 24 Sep 2011–Jan 2015 C 0.096 (0.080, 0.115) IgG capture ELISA (Panbio, Brisbane, Australia) Brazil Fortaleza 02–12 2 483 indirect IgG ELISA Zhang et al. 25 Nov 2019–Feb 2020 A 0.086 (0.024, 0.215) Panbio Dengue IgG nidirect ELISA Brazil Recife 05–65 6 2070 IgG for NS1 ELISA Braga et al. 26 Aug 2018–Feb 2019 A 0.052 (0.028, 0.080) in-house Brazil Tapera of Itarema (municipality) in state of Ceara 0–59+ 3 288 indirect IgG ELISA Sacramento et al.…”
Section: Resultsmentioning
confidence: 99%
“… 24 Sep 2011–Jan 2015 C 0.096 (0.080, 0.115) IgG capture ELISA (Panbio, Brisbane, Australia) Brazil Fortaleza 02–12 2 483 indirect IgG ELISA Zhang et al. 25 Nov 2019–Feb 2020 A 0.086 (0.024, 0.215) Panbio Dengue IgG nidirect ELISA Brazil Recife 05–65 6 2070 IgG for NS1 ELISA Braga et al. 26 Aug 2018–Feb 2019 A 0.052 (0.028, 0.080) in-house Brazil Tapera of Itarema (municipality) in state of Ceara 0–59+ 3 288 indirect IgG ELISA Sacramento et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies have also found a similar pattern regarding knowledge, attitudes and practices (KAPs) and seropositivity to DENV, Leptospira spp. or SARS-COV 2 [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Given the health risks of acquiring dengue, sufficient knowledge, positive attitudes, and proper practices (KAP) are crucial for the prevention and control of the virus [28]. Furthermore, high levels of KAP can empower individuals to take part in the necessary disease control and prevention programs [29].…”
Section: Introductionmentioning
confidence: 99%